Penerapan Metode Double Moving Average Dalam Peramalan Permintaan Produk Beras - Ikhwani, Riska; Siagian, Yessica; Marpaung, Nasrun (Building of Informatics, Technology and Science (BITS), 2022)
UD. Putra Tunggal is a trading business that sells people's basic needs such as rice, cooking oil, sugar and other basic needs of the community. This trading business requires forecasting in an effort to process data and produce accurate reports. This is done because UD. Putra Tunggal to determine the demand for rice is unpredictable, so he often experiences a lack of supply of rice to be purchased in serving the demand for rice needed by customers. In designing this system, the author uses the Double Moving Average (DMA) forecasting method for the decision support process in determining the amount of rice stock to be sold for the next month, using the calculation method. Forecasting application is made using visual basic net 2010 programming language with Microsoft Access for data base. From making the system an application can be produced that can control demand optimally and economically and with a high level of accuracy and can predict the amount of rice demand at UD. Putra Tunggal so that the forecast results can help trading businesses to avoid running out of rice demand stocks at UD. Putra Tunggal. The results of the forecasting of sales of CABE rice products 1 year ago, namely in January in 2021, it has been predicted that sales in January 2022 will decrease to 195 sacks of rice to be sold